Large abdominal cyst of the fetus: A rare diagnosis of neonatal megaduodenum - Dajia Wang; Zhibo Zhang; Yuzuo Bai (Elsevier, 2022)
We present a rare case of neonatal duodenal malformation. Herein, we provide a differential diagnosis for a large abdominal cyst in a prenatal fetus and explore the possible causes and treatment of neonatal megaduodenum. We retrospectively analyzed one case of megaduodenum from fetal examination to neonatal diagnosis and treatment. Ultrasonography of the fetus at 12 weeks' gestation revealed a cystic mass in the abdominal cavity, measuring about 0.7 cm × 0.5 cm × 0.4 cm. The cystic mass grew in equal proportion to the fetus. At 32 weeks' gestation, the peritoneal cystic mass was enlarged to 9.0 cm × 7.9 cm × 5.8 cm, and the mass was found to be communicating with the stomach. Intraoperatively, the mass was about 10-cm long and 6 cm in diameter. The duodenal papilla was located about 1.5 cm above the proximal junction. The megaduodenum was removed, and the distal and proximal intestines were anastomosed end-to-end. The patient recovered smoothly postoperatively and gained 550 g 1 month after discharge. The results of amniotic fluid high-throughput sequencing identified Seq [Grch37] del (16) (p12.2) Chr16: g.22000000_22440000del. There was a copy number deletion of about 0.44 Mb on the short arm of chromosome 16, which was suspected to be pathogenic and involved seven protein-coding genes. Histopathologically, in the same paraffin specimen, there was a mixture of stunted ganglion cells, ganglion dysplasia, and well-developed ganglion cells. Neonatal megaduodenum was considered as a differential diagnosis of the large cystic mass in the fetal abdomen. Further additional evidence was needed to prove whether the mutation was pathogenic, which also suggested that the etiology is related to genetic variation. The nerve plexus and ganglion cells were poorly developed, which further supported that the intestinal nerve abnormality was the etiology. Excision was safe and effective for treating megaduodenum.